Factors associated with stunting among children 0-23 months in Aceh: A cross-sectional study using SSGI 2021 - Aripin Ahmad; Abidah Nur; Teuku Muliadi; Nelly Marissa; Iflan Naufal; Marisa Marisa; Junaidi Junaidi; Fitrah Reynaldi; Eva Fitriyaningsih; Husnah Husnah; Muhammad Rizal Martua Damanik; Ardi Adji; Syuja' Rafiqi; Devita Annisa (AcTion: Aceh Nutrition Journal, 2024)
Stunting is a chronic health problem that affects children and has long-term implications for their cognitive development. The multifactorial causes of stunting require identification of the most dominant factors to facilitate effective interventions. This study aimed to analyze the factors associated with stunting in children under two years old in Aceh. This was a cross-sectional study involving 2,395 subjects aged 0-23 months. Data were obtained from the 2021 SSGI National Survey, consisting of stunting prevalence, child and family characteristics, household sanitation, universal health insurance ownership, breastfeeding and complementary feeding practices, immunization status, parenting and pregnancy classes, supplementary feeding, and food security. Logistic regression analysis was performed using 95% confidence intervals. The results showed a significant association between stunting and child sex, sanitation conditions, parental education, exclusive breastfeeding, complementary feeding practices, immunization status, micronutrient supplementation, and breastfeeding duration (p<0,05). In conclusion, the factors associated with stunting in children aged 0-23 months in Aceh are sanitation, parental education, exclusive breastfeeding, complementary feeding practices, immunization, micronutrient supplementation, and breastfeeding duration. This study highlights the importance of improved nutrition education, family support, immunization coverage, and environmental sanitation to reduce the prevalence of stunting among young children in Aceh